Process engineering for bioflavour production with metabolically active yeasts – a mini‐review. Issue 1 (16th December 2014) - Carlquist, Magnus; Gibson, Brian; Karagul Yuceer, Yonca; Paraskevopoulou, Adamantini; Sandell, Mari; Angelov, Angel I.; Gotcheva, Velitchka; Angelov, Angel D.; Etschmann, Marlene; de Billerbeck, Gustavo M.; Lidén, Gunnar
Abstract Flavours are biologically active molecules of large commercial interest in the food, cosmetics, detergent and pharmaceutical industries. The production of flavours can take place by either extraction from plant materials, chemical synthesis, biological conversion of precursor molecules or de novo biosynthesis. The latter alternatives are gaining importance through the rapidly growing fields of systems biology and metabolic engineering, giving efficient production hosts for the so‐called 'bioflavours', which are natural flavour and/or fragrance compounds obtained with cell factories or enzymatic systems. Yeasts are potential production hosts for bioflavours. In this mini‐review, we give an overview of bioflavour production in yeasts from the process‐engineering perspective. Two specific examples, production of 2‐phenylethanol and vanillin, are used to illustrate the process challenges and strategies used. Copyright © 2014 John Wiley & Sons, Ltd.